Factor VIII A3 domain residues 1793–1795 represent a factor IXa-interactive site in the tenase complex - Takeyama, Masahiro; Furukawa, Shoko; Sasai, Kana; Horiuchi, Kaoru; Nogami, Keiji (Biochimica et biophysica acta. General subjects, 2023)
Factor (F)VIII functions as a cofactor in the tenase complex responsible for conversion of FX to FXa by FIXa. Earlier studies indicated that one of the FIXa-binding sites is located in residues 1811–1818 (crucially F1816) of the FVIII A3 domain. A putative, three-dimensional structure model of the FVIIIa molecule suggested that residues 1790–1798 form a V-shaped loop, and juxtapose residues 1811–1818 on the extended surface of FVIIIa. To examine FIXa molecular interactions in the clustered acidic sites of FVIII including residues 1790–1798. Specific ELISA's demonstrated that the synthetic peptides, encompassing residues 1790–1798 and 1811–1818, competitively inhibited the binding of FVIII light chain to active-site-blocked Glu-Gly-Arg-FIXa (EGR-FIXa) (IC50; 19.2 and 42.9 μM, respectively), in keeping with a possible role for the 1790–1798 in FIXa interactions. Surface plasmon resonance-based analyses demonstrated that variants of FVIII, in which the clustered acidic residues (E1793/E1794/D1793) or F1816 contained substituted alanine, bound to immobilized biotin labeled-Phe-Pro-Arg-FIXa (bFPR-FIXa) with a 1.5–2.2-fold greater KD compared to wild-type FVIII (WT). Similarly, FXa generation assays indicated that E1793A/E1794A/D1795A and F1816A mutants increased the Km by 1.6–2.8-fold relative to WT. Furthermore, E1793A/E1794A/D1795A/F1816A mutant showed that the Km was increased by 3.4-fold and the Vmax was decreased by 0.75-fold, compared to WT. Molecular dynamics simulation analyses revealed the subtle changes between WT and E1793A/E1794A/D1795A mutant, supportive of the contribution of these residues for FIXa interaction. The 1790–1798 region in the A3 domain, especially clustered acidic residues E1793/E1794/D1795, contains a FIXa-interactive site. •Factor (F) VIII functions as a cofactor responsible for conversion of FX to FXa by FIXa.•One of the FIXa-binding sites in residues 1811–1818 of the FVIII A3 domain was reported.•We found a novel FIXa-binding site in the 1790–1798 region of FVIII A3 domain.•Residues E1793, E1794, and D1795 was bound with FIXa.•Molecular dynamics simulation showed the structural change of E1793A-D1795A mutant.